Hot Spring Gas Geochemical Characteristics and Geological Implications of the Northern Yadong-Gulu Rift in the Tibetan Plateau - Yu, Xiaoli; Wei, Zhifu; Wang, Gen; Ma, Xueyun; Zhang, Ting; Yang, Hui; Li, Liwu; Zhou, Shixin; Wang, Xianbin (Frontiers in Earth Science, 2022)
To reveal the heat source and its formation mechanism of the northern Yadong-Gulu Rift (YGR), we analyzed the helium isotope, carbon isotope (δ13CCO2), CO2/3He and CH4/3He ratio of hot spring gases for tracing the sources of volatiles and discussing their geological significance. The results show that: helium is mainly derived from the crust, the radioactive decay of the thicker crust and granites provided more 4He lead to the low helium isotopes; thermal decomposition of carbonate rocks is the main source of CO2; CH4 may be of organic origin. To sum up, the gas geochemical characteristics of hot springs in the northern YGR indicate that the volatiles mainly derived from the crust. The crust/mantle heat flow ratios (qc/qm) calculated by helium isotopes cover a range of 0.84 ~ 1.48, suggested that the heat is mainly contributed by the crust. The crustal origin gas and heat flow demonstrates that the heat source beneath the northern YGR formed by the process of interior crust. Combined with geophysical data, we suggest that the stress heat caused by the collision of the Indo-Eurasian plate and the radiant heating of the crust lead to the heat source (partial melting) and provide heat for the thermal activities.